Effects of flotation and acid treatment on unburned carbon recovery from atmospheric circulating fluidized bed coal gasification fine ash and application evaluation of residual carbon. (December 2021) - Li, Jiawei; Chen, Zhichao; Yuan, Linxuan; Qiao, Yanyu; Yuan, Zhenhua; Zeng, Lingyan; Li, Zhengqi
Graphical abstract: Highlights: The pickling method increased the carbon content of the sample to 89.97%. The CGFA of acid treatment method can be the precursor of activated carbon. The flotation method has poor effect on the separation of water-containing CGFA. Both methods of flotation and acid treatent improve the reactivity of CGFA. Abstract: The high carbon content (20–60%) in coal gasification fine ash (CGFA) makes CGFA unable to be directly used in the building materials and ceramic industries, and can only be dissipated in landfills, which brings serious environmental safety problems. This paper uses physical (flotation method) and chemical (multi-stage pickling method) methods to treat CGFA, analyze the separated carbon, and evaluate its application. The carbon content of the filter cake ash (FCA) residual carbon recovered by the flotation method is slightly increased, and the carbon ash separation effect for the water-containing CGFA is poor. The carbon content of dry ash (DA) recovered carbon in acid treatment increased from 16.33% to 89.97%. The specific surface area of the acid-washed recovered carbon is 6–34 times that of the original sample, and the specific surface area of dry ash-HCl/HF/HCl (DA-CFC) is as high as 425.31 m 2 /g, and its pore structure network is more developed than before deashing. After pickling treatment, the microcrystalline structure changes, the carbon skeleton becomes looser, the degree of crosslinking decreases, and the reaction activity increases. The relative content of CC in the acid-washed recovered carbon increased by 6.4–46.3%, and the relative content of functional group CH bonds increased by 48.5–89.5%. Compared with the activation energy of the original sample, the activation energy E of the sample after flotation and acid treatment is reduced, and the reaction activity is enhanced. Flotation and pickling methods can improve the grade of fuel, and multi-stage pickling methods to obtain high specific surface area carbon can be used as a precursor for the preparation of activated carbon. Carbon-ash separation of DA by flotation method can be applied to fuel combustion, fine chemical industry, and road filling. However, for FCA, it is necessary to use a pickling scheme for carbon-ash separation to realize resource utilization and harmlessness.